Biofilm Effectivity of Ethanol Extracts (Casuarina equisetifolia) Leaves of the Bacteria Enterococcus faecalis - Debby Rosalina; Aprilia (Denta Journal Kedokteran Gigi, 2020)
Background: Enterococcus faecalis is one of the bacteria that can form biofilms that can cause persistent endodontic infections. Biofilm is the unity of microbial cell surface surrounded by a matrix of extracellular polymeric substances (EPS). The ethanol extracts of Casuarina equisetifolia leaves are known to have potentially bioactive compounds as antibacterials such as flavonoids, saponins, tannins, phenols, and alkaloids. Objective: To determine the power antibiofilm ethanol extracts of Casuarina equisetifolia leaves at multiple concentrations of the bacteria Enterococcus faecalis. Methods: This study is an experimental research design post-test only control group design. The sample divided into 5 groups consisted of positive control Enterococcus faecalis in media Trypticase Soy Broth (TSB)+DMSO 1%, and 4 treatment groups of ethanol extracts of Casuarina equisetifolia leaves a concentration of 0,5%, 1%, 1,5%, and 2%. Biofilm is made using Enterococcus faecalis ATCC 29212 bacteria were cultured on TSB media were incubated for 1x24 hours. 0,1 ml of the bacteria Enterococcus faecalis with a concentration of 106 put on a plate micro titter then done using crystal violet staining. Biofilm-checked by measuring optical density (OD) values ​​using the ELISA reader. Data analysis used Kruskal-Wallis followed by Mann-Whitney test. Results: The ethanol extracts Casuarina equisetifolia leaves on the growth of Enterococcus faecalis bacteria indicate the presence of power antibiofilm. The results mean % mortality of bacteria (p<0.05) were significant in all groups that have the power antibiofilm effectiveness as against the growth of bacteria Enterococcus faecalis. Conclusion: The ethanol extracts Casuarina equisetifolia leave have antibiofilm power against bacterial growth Enterococcus faecalis.